2024
DOI: 10.1038/s41467-024-45475-w
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of plasma ctDNA fraction and prognostic implications of liquid biopsy in advanced prostate cancer

Nicolette M. Fonseca,
Corinne Maurice-Dror,
Cameron Herberts
et al.

Abstract: No consensus strategies exist for prognosticating metastatic castration-resistant prostate cancer (mCRPC). Circulating tumor DNA fraction (ctDNA%) is increasingly reported by commercial and laboratory tests but its utility for risk stratification is unclear. Here, we intersect ctDNA%, treatment outcomes, and clinical characteristics across 738 plasma samples from 491 male mCRPC patients from two randomized multicentre phase II trials and a prospective province-wide blood biobanking program. ctDNA% correlates w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 75 publications
0
0
0
Order By: Relevance
“…In two prospective observational multicenter studies, the researchers examined the ctDNA fraction (the proportion of total plasma cell-free DNA that is tumor-derived) in 81 patients with mCRPC before start of therapy and 4-weeks after treatment initiation. Baseline ctDNA was detected (≥1% ctDNA) in 59% of patients and the detection had strong prognostic implications, consistent with literature [ 14 16 ]. Importantly, persistent ctDNA detection 4-weeks after treatment initiation was associated with a 4.8 times shorter progression free survival (PFS) and 5.5 times shorter overall survival (OS) compared to patients with undetected ctDNA at baseline and 4-weeks.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…In two prospective observational multicenter studies, the researchers examined the ctDNA fraction (the proportion of total plasma cell-free DNA that is tumor-derived) in 81 patients with mCRPC before start of therapy and 4-weeks after treatment initiation. Baseline ctDNA was detected (≥1% ctDNA) in 59% of patients and the detection had strong prognostic implications, consistent with literature [ 14 16 ]. Importantly, persistent ctDNA detection 4-weeks after treatment initiation was associated with a 4.8 times shorter progression free survival (PFS) and 5.5 times shorter overall survival (OS) compared to patients with undetected ctDNA at baseline and 4-weeks.…”
supporting
confidence: 89%
“…Additionally, there are different assays to assess ctDNA fraction in prostate cancer all with different limits of detections. The custom assay used by Tolmeijer et al has been shown to have strong prognostic utility for baseline ctDNA assessments [ 14 16 ]. The limit of detection of this assay is approximately 1%, which is in line with most other commercially available assays [ 21 ].…”
mentioning
confidence: 99%
“…In another work, Khan et al [10] explored the potential of ctDNA to detect RAS mutants as an early signal of resistance in colorectal cancer. These mathematical models, as well as other computational studies [26, 2, 6] have demonstrated the tremendous potential of using observed ctDNA dynamics to extract insights about tumor biologic processes and response to treatment. Here, using simulated virtual patient cohorts, we develop dynamic biomarkers predictive of treatment response using early, frequent ctDNA sampling.…”
Section: Introductionmentioning
confidence: 99%